Vertebral Artery Anomalies at the Craniovertebral Junction: A Case Report and Review of the Literature - Abtahi, Amir M.; Brodke, Darrel S.; Lawrence, Brandon D. (Evidence-Based Spine-Care Journal, 2014)
Study Design Case report.Objective The objective of this study was to report a case of an unstable C1 burst fracture in the setting of a vertebral artery anomaly at the craniovertebral junction.Methods A 55-year-old man was admitted to the hospital with severe neck pain after falling approximately 15 feet and landing on his head. Computed tomography scan of the cervical spine revealed an unstable fracture of the C1 ring with magnetic resonance imaging evidence of a transverse ligament rupture as well as a congenital synchondrosis of the posterior arch of C1. He was neurologically intact. CT angiography (CTA) of the neck revealed an anomalous course of the right vertebral artery at the C1–C2 level.Results Surgical intervention consisted of occiput–C3 fusion, thus avoiding the placement of C1 lateral mass screws and risking vertebral artery injury.Conclusion We present a case of an unstable C1 burst fracture with an anomalous course of the right vertebral artery demonstrated by CTA. The presence of vertebral artery anomalies at the craniovertebral junction may prevent safe placement of C1 lateral mass screws and therefore influence the treatment options for upper cervical spine pathologies. To minimize the risk of vertebral artery injury, we elected to perform an occiput to C3 fusion. Thorough assessment of the vascular anatomy is recommended before operative intervention in the upper cervical spine to minimize the risk of complications.
Keywords: vertebral artery; C1 synchondrosis; C1 burst fracture